Age-specific association between moderate-to-vigorous physical activity and bone health: insights from a universal pDXA screening cohort in rural China - Huang, Bin; Yang, Minzhi; Zhao, Wenting; Wu, Qiong; Xiao, Ying; Liu, Qin; Li, Fangfang; Du, Huan (Frontiers in Endocrinology, 2026)
ObjectiveTo identify age-specific and gender-specific correlations between moderate-to-vigorous physical activity (MVPA) and forearm bone mineral density (BMD, via pDXA) in rural elderly (≥ 60 years) and define optimal bone health intervention windows.MethodsCross-sectional analysis of 3, 530 participants from a universal pDXA screening cohort (Suzhou, 2021). BMD was expressed as forearm T-scores; MVPA was categorized (low: < 150, moderate: 150–300, high: > 300 min/week) via WHO GPAQ. Age was stratified into 60–69, 70–79, ≥ 80 years. Statistical analyses included Kruskal-Wallis H test, Spearman correlation, and multivariable linear regression with MVPA × age group and MVPA × gender interaction terms.ResultsMedian T-score was -2.1 (IQR: -3.9 to -0.8). T-scores decreased with age (-1.8 vs. -2.3 vs. -2.9, p < 0.001). MVPA × age group interaction was significant (p = 0.008), with high MVPA associated with higher T-scores only in 60–69 years (-1.5 vs. -2.0, p=0.003). The MVPA-BMD association was stronger in females (β = 0.27) than males (β = 0.16). Female gender (β = -0.52), older age (β = -0.03/year), and low MVPA (β = -0.21) independently predicted lower T-scores (all p < 0.001).ConclusionThe association between MVPA and BMD is age-dependent and gender-specific, with the strongest positive correlation observed in 60–69 years females. These findings suggest a potential age-specific intervention window for MVPA to promote bone health in rural elderly populations, but causal inferences are limited by the cross-sectional design.